EFEKTIVITAS PENGGUNAAN MODEL INKUIRI TERBIMBING DENGAN METODE DEMONSTRASI DALAM MENINGKATKAN HASIL - Febrian Junaidy; Alfrits Komansilan; Jimmy Lolowang (Charm Sains: Jurnal Pendidikan Fisika, 2021)
This research is related to the use of guided inquiry models with demonstration methods. Research has been conducted to determine the extent to which there is an increase in student learning outcomes after the physics learning class action is carried out with the guided inquiry model using the demonstration method. The research method is a classroom action research (CAR) method that is applied in class X SMK. The results showed that the action of learning can improve student learning outcomes. The increase in learning outcomes can be seen from the increase in the average value in the first cycle and second cycle also an increase in the percentage of mastery learning. Because of that the use of inquiry guidance models using demonstration methods can be used as an alternative in learning science physics in high school. Learning outcomes can be seen from the increase in the average value in the first cycle and second cycle also an increase in the percentage of mastery learning. Because of that the use of inquiry guidance models using demonstration methods can be used as an alternative in learning science physics in high school.